LITERATURE REVIEW: PENILAIAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DI LABORATORIUM KIMIA - Hilda Aprilia Azizi (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
The chemical laboratory “is a location for experiments and research that can lead to accidents. The Synthetic Research Center has a high accident rate with an average of 18 cases each year. Raw materials, work processes, products and generated waste (liquid, solid and gaseous) are all potential hazards in the workplace. Physical and mental factors both play a role in work accidents. Physical factors, such as unsafe working conditions, for example. While the human factor is the behavior of workers who violate safety rules due to carelessness, drowsiness, fatigue, and other factors. various accidents in the workplace which are primarily caused by human error. Unwanted incidents or events that cause human losses, property damage, or process losses are work accidents” (Piri, 2012).